The role of chromatin remodeller ATRX in gene expression - Shen, Y (2022)
ATRX is a chromatin remodeller involved in a wide range of nuclear processes, including transcription. Germline mutations in ATRX give rise to alpha- thalassaemia/intellectual disability X-linked (ATR-X) syndrome and downregulate alpha globin expression through a mechanism which is poorly understood. To understand how ATRX regulates gene expression, here I use alpha thalassaemia as an exemplar to study how ATRX loss downregulates alpha globin expression, which would provide insights into understanding the general gene regulation mechanism of ATRX. Specifically, I aim to recapitulate the alpha thalassaemia phenotype observed in ATR-X syndrome patients in an ATRX deficient erythroid cell system, and then to determine the molecular mechanisms that cause perturbed alpha globin expression.